Philosophical reflections on the meaning and substance to the concept “politics” territories in Bulgarian - Kuytov, Ahmed (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
The current paper is intended to raise discussion whose outcome is devising a concept, which corresponds to the true essence of the word “politician”. We need for establishment of what a concept is because today this word is used very widely. With the term “politician” determination people who are actually a distant of politics. Because a politician needs to implement policies through which people who chose to live peacefully, calmly and safely. A Bulgarian people, the last 200 years, live constantly on the edge, often even fails of it. Reaches the edge, through the actions of those individuals who unfairly characterized as politicians